2017
DOI: 10.1525/elementa.238
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical characterization of municipal compost to support urban agriculture and limit childhood lead exposure from resuspended urban soils

Abstract: Chronic low-level lead exposure among low-income minority children is an urgent environmental justice issue. Addressing this ubiquitous urban public health crisis requires a new transdisciplinary paradigm. The primary goals of this work are to inform best practices for urban gardeners working in lead contaminated soils and to reimagine urban organic waste management schemes to produce compost, which when covering or mixed with urban soil, could minimize lead exposure. We investigate bulk and bioaccessible lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…Other studies have also found a linear relationship between total and bioaccessible Pb, though the slope of the regression line varies by study location (Fitzstevens et al, 2017). Other studies have also found a linear relationship between total and bioaccessible Pb, though the slope of the regression line varies by study location (Fitzstevens et al, 2017).…”
Section: Drivers Of Pb Bioaccessibilitymentioning
confidence: 97%
See 4 more Smart Citations
“…Other studies have also found a linear relationship between total and bioaccessible Pb, though the slope of the regression line varies by study location (Fitzstevens et al, 2017). Other studies have also found a linear relationship between total and bioaccessible Pb, though the slope of the regression line varies by study location (Fitzstevens et al, 2017).…”
Section: Drivers Of Pb Bioaccessibilitymentioning
confidence: 97%
“…Previous studies have shown that compost dilutes total soil Pb concentrations Clark et al, 2008;Clarke et al, 2015;Fitzstevens et al, 2017). Since total Pb is directly proportional to bioaccessible Pb and compost binds Pb more effectively than soil, compost application also reduces urban gardeners' exposure to bioaccessible Pb through dilution and limiting Pb solubility (Table 1).…”
Section: Benefits Of Compost Use In Urban Agriculturementioning
confidence: 97%
See 3 more Smart Citations